The SmartAG partner: CCAFS East Africa Quarterly Newsletter, July - September 2016 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
We are pleased to share with you the third issue of the SmartAg Partner quarterly newsletter, highlighting ongoing research and policy engagement from July to September 2016. To mark World Youth Skills Day (WYSD) on July 15, CCAFS held an online discussion forum on Youth Engagement in Climate Smart Agriculture (CSA) and the 2030 Agenda for Sustainable Development. Find out what skills young farmers need to adopt CSA. CCAFS also organized a farmer field day in partnership with Friends of Katuk Odeyo (FOKO) and Kapsokale, two key communitybased organizations (CBOs) working at the Nyando climate-smart villages (CSVs). Also from the field, find out how Galla goats are changing the lives of farmers in Nyando and how improved fodder is contributing towards reducing climate risks. In September, the Africa Group of Negotiators (AGN) in partnership with African Group of Negotiators Expert Support (AGNES) convened a pre-COP meeting in Nairobi to discuss the possible elements of a draft decision on agriculture taking into consideration the provisions of the Paris Agreement. Read more about the critical issues identified by the AGN for discussion at the 22nd session of the Conference of the Parties (COP22). In Uganda, CCAFS researchers engaged with policymakers to discuss the need for gender responsive policies and strategies to respond to climate change in agriculture. Find out more about the discussions. Within the framework of the CCAFS project “Policy Action for Climate Change Adaptation (PACCA)”, the International Institute of Tropical Agriculture (IITA) has partnered with the Parliamentary Forum on Climate Change and the Parliamentary Forum on Food Security, Population and Development to strengthen the national research-base on agriculture, climate change and food security in the country. Learn more from the outcomes of this partnership. In Rwanda, meteorology experts were trained on the application of the Climate Predictability Tool (CPT). Read more about the training and development of downscaled seasonal forecasts. A recently released working paper by CCAFS and ICRAF compiles evidence-based opportunities for out-scaling climate-smart agriculture in East Africa from 175 peer-reviewed and grey literature studies.